A novel chromone-based as a potential inhibitor of ULK1 that modulates autophagy and induces apoptosis in colon cancer - Shamsudin, Nur Farisya; Leong, Sze-Wei; Koeberle, Andreas; Suriya, Utid; Rungrotmongkol, Thanyada; Chia, Suet Lin; Taher, Muhammad; Haris @ Harith, Muhammad Salahuddin; Alshwyeh, Hussah Abdullah; Alosaimi, Areej A; Mediani, Ahmed; Ilowefah, Muna Abdulsalam; et al. (Taylor and Francis Ltd., 2024)
Aim: Chromones are promising for anticancer drug development.